Synthesizing Mind as a 21st Century Competence in Education: A Systematic Literature Review - Rudolf Ngalu; Gatot Afrianto; Mami Hajaroh; Jumadi Jumadi (Lembaga Bale Literasi, 2025)
The synthesizing mind is a higher-order cognitive competency that is important in 21st-century education because it helps students integrate information, build coherent understanding, and generate new ideas. However, studies that systematically map the development, themes, and educational implications of this concept remain limited. Therefore, this study aims to analyze literature on the synthesizing mind in educational contexts using a Systematic Literature Review (SLR) approach. The study followed structured stages, including keyword selection, literature search, article screening based on inclusion and exclusion criteria, and thematic and bibliometric analysis. The analysis focused on publication trends, conceptual relationships, implementation patterns, and research gaps. The findings show that the synthesizing mind has been studied across various disciplines and is commonly associated with project-based learning, collaborative learning, digital technology, and reflective learning. The literature also indicates that synthesizing ability is influenced by cognitive factors, learning experiences, socio-cultural contexts, and curriculum design. Despite these developments, several gaps remain, particularly in the development of measurement instruments, implementation across educational levels, and evaluation of long-term impacts on students’ higher-order thinking skills. This study concludes that the synthesizing mind is a crucial competency for strengthening critical, creative, and integrative thinking in 21st-century education.